2008
DOI: 10.1055/s-2008-1034373
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Efficacy of Calceolarioside A against Experimental Visceral Leishmaniasis

Abstract: Bioactivity-guided fractionation has led to the successful isolation of calceolarioside A ( 1) from the methanolic extract of night jasmine leaves. The in vitro antileishmanial activity of compound 1 was determined (IC (50) = 20 microg/mL). Its IN VIVO efficacy was noted at 20 mg/kg body weight when it reduced the hepatic and splenic parasite burden by 79 and 84 %, respectively, in an established model of L. donovani Ag83 infected golden hamster. Furthermore, synergistic potentiations of compound 1 at 20 mg/kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
(21 reference statements)
0
4
0
Order By: Relevance
“…In addition, verbascoside also presented analgesic and CNS depressant activity (Grice et al, 2003;Pieretti et al, 1992). Moreover, calceolarioside A and iso-verbascoside have shown leishmanicidal activity (Emam et al, 1995;Poddara et al, 2008) Characteristic compounds from Mansoa alliacea (Bignoniaceae) are sulfoxides (mainly alliin) and other sulfur compounds. Dunstan et al (1997) showed that M. alliacea extracts have antinflammatory activity in rats and COX-1 inhibitory activity.…”
Section: Function Of Plants In Strict Dietsmentioning
confidence: 99%
“…In addition, verbascoside also presented analgesic and CNS depressant activity (Grice et al, 2003;Pieretti et al, 1992). Moreover, calceolarioside A and iso-verbascoside have shown leishmanicidal activity (Emam et al, 1995;Poddara et al, 2008) Characteristic compounds from Mansoa alliacea (Bignoniaceae) are sulfoxides (mainly alliin) and other sulfur compounds. Dunstan et al (1997) showed that M. alliacea extracts have antinflammatory activity in rats and COX-1 inhibitory activity.…”
Section: Function Of Plants In Strict Dietsmentioning
confidence: 99%
“…Its in vivo efficacy was noted at 20 mg/kg body weight when it reduced the hepatic and splenic parasite burden by 79 and 84 %, respectively, in an established model of L. donovani Ag83 infected golden hamster. This was the first report describing the isolation of compound calceolarioside A from NAT and the first demonstration of its potent activity against visceral leishmaniasis 34 .…”
Section: Chemical Constituentsmentioning
confidence: 91%
“…The important phytoconstituents isolated from leaves are triterpenoid (oleanolic acids and nyctanthic acids) (Anjaneyulu and Murty 1981), sterol (b sitosterol) (Sen and Singh 1964), and glycoside calceolarioside-A (Poddar et al 2008). Nyctanthoside (Rimpler and Junghanns 1975), a new iridoid glycoside (cyclohexylethanoid rengyolone) (Tuntiwachwuttikul et al 2003), and carotenoid glycoside (b-digentiobioside ester of a-crocetin or crocin-1) (Dhingra et al 1976) were isolated from flowers.…”
Section: Introductionmentioning
confidence: 99%
“…Among all these compounds, b-sitosterol showed analgesic and anti-inflammatory activities (Nirmal et al 2012a, b). Antileishmanial activities of calceolarioside-A (Poddar et al 2008) and iridoid glycosides (A, B, and C) (Shukla et al 2011) have been reported. Antimalarial property of rengyolone and its acetate was reported by Tuntiwachwuttikul et al (2003).…”
Section: Introductionmentioning
confidence: 99%